2016
DOI: 10.1589/jpts.28.90
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neck flexion restriction on sternocleidomastoid and abdominal muscle activity during curl-up exercises

Abstract: [Purpose] The purpose of this study was to investigate the effect of neck flexion restriction on sternocleidomastoid (SCM), rectus abdominis (RA), and external oblique (EO) muscle activity during a traditional curl-up exercise and a curl-up with neck flexion restriction. [Subjects] In total, 13 healthy male subjects volunteered for this study. [Methods] All subjects performed a traditional curl-up exercise and a curl-up exercise in which neck flexion was restricted by the subject’s hand. Surface electromyograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In another study, in which muscle activities during curl-ups performed at different trunk flexion angles were examined, greater flexion angle induced more activity of the upper RA, while a reduced flexion angle was advantageous for activating the lower RA ( Kim et al, 2015 ). More recently, Lee et al (2016) suggested that restriction of neck flexion could generate greater activity of the RA and external oblique (EO) abdominis ( Lee et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, in which muscle activities during curl-ups performed at different trunk flexion angles were examined, greater flexion angle induced more activity of the upper RA, while a reduced flexion angle was advantageous for activating the lower RA ( Kim et al, 2015 ). More recently, Lee et al (2016) suggested that restriction of neck flexion could generate greater activity of the RA and external oblique (EO) abdominis ( Lee et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The "OTAGO exercise programme" (Campbell et al, 1997) is an individually tailored programme that was originally designed to be carried out in a client's home by a physiotherapist or trained instructor. Park and Chang (2016) conducted a small study (N = 8) on the effectiveness of the "OTAGO" on the falls efficacy, quality of life and activities of daily living (ADLs) of older adults who had experienced a stroke. This was carried out by two occupational therapists alongside four exercise assistants in the USA.…”
Section: 1mentioning
confidence: 99%
“…The study found statistically significant improvements with fear of falling, but non-significant results with quality of life and ADL functioning. However, Park and Chang's (2016) sample consisted of a small group (N = 8) of older adults who had experienced a stroke, potentially limiting the generalisability of the results to all community-dwelling older adults who are at risk of falling. Nevertheless, Thomas et al (2010) have shown that the "OTAGO" reduces the risk of death and rate of falls in older adults living in the community by 35 per cent, while Carande-Kulis et al (2015) conducted a cost-benefit analysis and concluded that the "OTAGO" provided positive net benefits.…”
Section: 1mentioning
confidence: 99%